Koncepcja modernizacji Rosji w okresie prezydentury Dmitrija Miedwiediewa (2008-2012) - Czachor, Rafał (Przegląd Wschodnioeuropejski, 2023)
In contrast to his predecessor, President Dmitry Medvedev pushed Russia into a wave of socio-economic changes. His only term in the years 2008-2012 was dominated by the concept of modernization, which included democratization, market-oriented reforms, anti-corruption campaigns, and the support of civil society. Nevertheless, the results of the modernization program were modest. The present paper aims to present the cir-cumstances of the introduction of modernization, its content, criticism, and the reasons for its decay. The author argues that modernization was a personal initiative of D. Medvedev and stemmed from his preoccupations with new technologies and contemporary models of governance. At the end of D. Medvedev’s term, the concept of modernization disappeared from Russia’s public space and was replaced by a new rhetoric of “strong statehood” declared by Vladimir Putin.